Influence of Beer Brand Identification on Taste Perception - Allison, Ralph I.; Uhl, Kenneth P. (Journal of Marketing Research, 1964)
As a company tries to find the factors accounting for strong and weak markets, typical consumer explanations for both tend to be in terms of the physical attributes of the product. Carling Brewing Company used a relatively inexpensive experiment to help dichotomize contributing influences as being either product or marketing oriented and, also, to indicate the magnitude of the marketing influence for various brands. The experiment involved the use of groups of beer drinkers that tasted (drank) and rated beer from nude bottles and from labeled bottles.